POTENSI DAN TANTANGAN BLUE ECONOMY DALAM MENDUKUNG PERTUMBUHAN EKONOMI DI INDONESIA: KAJIAN LITERATUR - Marihot Nasution (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
The blue economy is an important issue because healthy oceans provide jobs and food, sustain economic growth, regulate the climate, and support the well-being of coastal communities. Billions of people around the world —especially the world's poorest— rely on healthy oceans for jobs and food, underscoring the urgent need to use, manage and sustainably protect this natural resource. This study examines the potential and challenges in each sector of the marine industry faced by the Indonesian government in implementing the blue economy concept and increasing economic growth. the study was carried out by conducting a literature study on blue economy practices that had been applied and studied previously. In assessing the contribution of blue economy-supporting sectors to the economy, it is evident that Indonesia has abundant potential. The biggest contribution can be seen from the fisheries sector, either in the form of capture fisheries or aquaculture. However, of all the industrial sectors in the blue economy, Indonesia has not fully developed the renewable energy, bio-economy, and biotechnology sectors optimally.